Golden Promise barley (Hordeum vulgare) is a suitable candidate model host for investigation interaction with Heterodera avenae - Shu-jie LUO; Ling-an KONG; Huan PENG; Wen-kun HUANG; Jiang-kuan CUI; Jing LIU; Fen QIAO; Heng JIAN; De-liang PENG (Journal of Integrative Agriculture, 2017)
Heterodera avenae (cereal cyst nematode, CCN) infects many cereal crops and causes serious yield losses worldwide. Interaction studies investigating H. avenae and its hosts are still in their infancy. In this study, a barley model plant, the Hordeum vulgare cultivar Golden Promise, was investigated for its potential as a candidate model host to study its interaction with H. avenae. CCN-infective juveniles were attracted by the root tips and gathered around the root elongation zones of Golden Promise on 0.7% water agar plates. The juveniles invaded the roots and developed successfully until maturation at 40 days after inoculation in sterile sand soil. The cryotomy and syncytium measurements indicated that the syncytia enlarged gradually throughout the development of the nematodes and caused the corresponding root regions to swell obviously. Quantitative real-time PCR analysis showed that the down-regulation of defence-related barley genes and up-regulation of development-related barley genes contribute to the understanding of compatible interaction between H. avenae and Golden Promise. Barley stripe mosaic virus (BSMV) virus-induced gene silencing (VIGS) can be used in the roots of Golden Promise. In conclusion, the Hordeum vulgare cultivar Golden Promise is a suitable candidate model host for interaction studies with Heterodera avenae. The studies presented above document the first CCN host that not only has published genome context but also be compatible to BSMV VIGS.